A direct control based maximum power point tracking method for photovoltaic system under partial shading conditions using particle swarm optimization algorithm - Ishaque, Kashif (2012)
This paper presents maximum power point tracking (MPPT) of photovoltaic (PV) system using particle swarm optimization (PSO) algorithm. The key advantage of the proposed technique is the elimination of PI control loops using direct duty cycle control method. Furthermore, since the PSO is based on optimized search method, it overcomes the common drawback of the conventional MPPT, i.e. the inability to track the global maximum point (GP) of PV array under partial shading conditions. The algorithm is employed on a buck-boost converter and tested experimentally using a PV array simulator. Ten irradiance patterns are imposed on the array, the majority of which include various partial shading patterns. Compared to the conventional direct duty cycle method, the proposed method performs excellently under all shading conditions. Finally, the performance of the proposed method is tested using the measured data of a tropical country (Malaysia) from 8.00 am to 6.00 pm. For the 10 h (daytime) irradiance and temperature profile, it yields an average MPPT efficiency of 99.5%.